RESEARCH ON DISTRIBUTION OF DYNAMIC LOAD FACTOR OF TRANSMISSION BOX BASED ON LOAD SPECTRUM - ZHENG SongLin; MA Jiong; ZHAO LiHui; YU WeiYi; YAO ShouWen (Jixie qiangdu)
In view of the excess strength and the excessive quality of a comprehensive transmission box which belongs to special vehicle, it is necessary to optimize box further. In the optimization process, based on the empirical formula of the rotational torque a larger dynamic load factor is calculated by using traditional method,which reduces the subsequent optimization space. Therefore, the dynamic load factors in the process of stationary transmission are studied based on the load spectrum. Firstly, the box body was tested by bench test, then the load spectrum of the dangerous part was measured. Secondly, the dynamic load factors in a stationary time history were obtained by dealing with these load spectrum. Thirdly, the maximum likelihood method and the goodness of fit AD value were used to identify and validate these dynamic load factors. Finally the dynamic load factor was obtained at 99 th percentile. The 99 th percentile dynamic load factor was compared with the dynamic load factor obtained from the empirical formula. The results show that under the condition of smooth transmission, the empirical formula is larger, the structural design is conservative, and the 99 th percentile dynamic load factor is reasonable, which is helpful to the realization of the lightweight design.